Efektifitas Penerapan Model Pembuat Keputusan dalam Proses Pengembangan Produk Pangan Baru - Ulfiana Anika Sari; Feri Kusnandar; Dede Robiatul Adawiyah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2015)
Portfolio management is essential to support food companies in the selection of new food product development (NFPD) projects. This is a tool to ensure that a food company performs enough of right NFPD projects to put the business objective and strategy into action. The objectives of this study were (1) to develop criteria for approval in each gate of NFPD process, (2) to measure the effectiveness of these criteria from the cost reduction advantage, and (3) to evaluate the performance of the developed NFPD process. This study developed criteria for approval as an integrated decision making process (starting from orientation, creation, preparation to implementation) to help the selection of projects. The improved NFPD process minimized the risk of project failure and gave more certain success of the new product launch in the market. Its implementation reduced the failure cost of projects. The company spent 40% of the allocated budget for the projects that completed all the stages and went through all the gates until the launch. For the projects that were either on hold or cancelled, the company spent 20.8% of the allocated budget. The underspent budget of 39.2% were then reallocated for new project initiatives. The developed NFFD model was considered effective by the company management.